The role of IL-24 as a pro-inflammatory cytokine in some Iraqi rheumatoid arthritis patients - Sattar Brissm Hassan,; Hanaa Naji Abdullah,; Khalied Yassin Zakair, (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the role of interleukin-24 as a pro-inflammatory cytokine among female rheumatoid arthritis patients, and its correlation with clinical parameters. Method: The case-control study was conducted from April to July 2021 at the Baghdad Teaching Hospital and Yarmouk Teaching Hospital, Iraq, and comprised women aged 26-60 years in the Al-Karkh district having rheumatoid arthritis diagnosed by a rheumatologist, and healthy controls matched for age and gender. Data was analysed using SPSS 28. Results: Of the 118 subjects, 76(64.4%) were patients with mean age 45.38±1.23 years, and 42(35.6%) were controls with mean age 46.48±2.02 years. Rheumatoid factor level was highly significant among the cases 37.30±2.50mg/L compared to the controls 4.91±0.53mg/L (p Less than or Equal to 0.05), and similar was the case with anti-cyclic citrullinated peptides 63.04±2.82U/mL versus 14.02±0.30U/mL (p Less than or Equal to 0.05). Serum interleukin-24 was considerably elevated in patients 157.52±9.40 compared to controls 34.75±3.06 (p Less than or Equal to 0.05). Interleukin-24 had a significant positive correlation with rheumatoid factor, and a significant negative correlation with C-reactive protein and erythrocyte sedimentation rate (p<0.05). Conclusion: Patients with rheumatoid arthritis had higher interleukin-24 serum levels than healthy controls, indicating that interleukin-24 may be a significant marker in rheumatoid arthritis diagnosis. Keywords: Protein, Antibodies, Cytokines, Arthritis, Rheumatoid.